Analysis of Surface Fault-Rupture Characteristics Resulting from the 6 February 2023 (Mw:7.6) Ekinozu Earthquake along the Ciglik Fault (Malatya-Dogansehir-Eskikoy) - Kocbulut, Fikret; Softa, Mustafa; Akgun, Elif; Kosaroglu, Sinan; Otlu, Nazmi (Afet ve Acil Durum Yonetimi Baskanligi (AFAD), 2024)
In this study, we analyze the surface rupture caused by the Kahramanmaras/Ekinozu (Mw: 7.6) Earthquake of February 6, 2023, along the Eastern Anatolian Fault Zone. The rupture, observed between the Do?ansehir district and Eskikoy town in Malatya province, was mapped at a scale of 1/25000. Additionally, we investigate the deep continuation of the rupture and quantify the resulting deformation. Our aim is to determine the width of deformation and vertical displacements, providing insights into its complex features. In surface rupture studies, it was determined that (i) the approximately 11 km mapped surface rupture between Malatya province's Do?ansehir district and Eskikoy town aligns with the previously identified Ciglik fault, (ii) the deformation width of the surface rupture ranges from 3.4 meters to 8.3 meters, with the most significant left-lateral displacement observed near the town of Ciglik reaching 95 cm, concurrently with a vertical displacement of 75 cm. © 2024 Afet ve Acil Durum Yonetimi Baskanligi (AFAD). All rights reserved.
6 Şubat 2023 (Mw:7.6) Ekinözü Depremi Yüzey Kiri?inin Çi?lik Fayi (Malatya-Do?anşehir-Eskiköy) Boyunca Karakteristik Analizi
Keywords: Ciglik Fault; East Anatolian Fault Zone; Kahramanmaras (Ekinozu) Earthquake; Surface fault-rupture